Optimalisasi Kecerdasan Majemuk Anak Usia Dini dengan Permainan Tradisional Batu Serimbang Usia 5-6 Tahun di RA Kurnia 2 Marelan - Asriyani Pasaribu; Puspita Rima Melati Harahap; Rini Lestari Siregar; Sabiah Ainul Rizki Mardiah; Trie Ananda Mawaddah; Masganti Sitorus (Journal on Education, 2023)
Multiple intelligences have now become common knowledge for educators. Every child has their own intelligence. Initially, intelligence only meant the value of brain intelligence. Therefore, all educators, especially in early childhood education (PAUD), must be able to recognize the potential of students to contribute to character development and self-confidence in overcoming challenges. The purpose of this study was to determine the optimization of multiple intelligences for early childhood with the traditional game of Batu Serimbang aged 5-6 years at RA Kurnia 2 Marelan. This research uses classroom action research (PTK) in collaboration with teachers, school principals, and school staff. The subjects in this study were 15 children. Data was collected using child ability test sheets, observations, field notes, and documentation. The results showed that the ability of children's traditional stone serimbang games in the first cycle of 20% of the children received an assessment of developing according to expectations and in the second cycle 80% of children who received an assessment of developing as expected and developing very well.